Bonnet-Bouveret syndrome A new case and literature review - Machín, Mariella; Colet, Andrés (Cirugía del Uruguay, 2004)
Biliary ileus is the mechanic occlusion caused by one or more gal/ stones which press on a sector of the intestine. Duodenal pyloric occlusion due to gal/ stones is the highest bi/iary ileus, commonly known as Bouveret's syndrome. The paper contains an ana/ysis of pathogenesis, physiopathology, clínica/ aspects and methods for the diagnosis and treatment of this particular syndrome. Final/y the paper describes a clinica/ case, with analysis of the patient's characteristics and the treatment prescribed.